Biofeedback in psychomotor training. Two month course results - Ye. M. Mernaya; A. V. Kondratenko; O. Kondratenko; O. M. Bazanova (Бюллетень сибирской медицины, 2010)
With the aim to compare the impact of usual training and training with the use of biofeedback, the psychometric and electrophysiological features of 36 musical students were investigated. Two month biofeedback training caused increase in self actualization, improving the musical performance score, decrease state and trait anxiety, increase of the individual adjusted alpha-2 indices, but theta-, alpha-1 and beta- activities did not change. Optimal psychomotor reaction for usual self practice (enhancement in alphaactivity and decrease in muscle tension) was achieved during biofeedback training. Training efficiency depended on the baseline electropsysiological features of optimal functioning: peak frequency, band width, power and coherence in individual alpha range, reaction activation. It was concluded that upper alpha stimulating and EMG decreasing biofeedback training leads to development of optimal psychomotor behavioral strategy.